Different strategies to attenuate the reproductive toxicity of ZnO nanoparticles - Vassal, Mariana Fontoura (2021)
Zinc oxide nanoparticles (ZnO NPs) are between the most synthesized metal oxide nanoparticles (MONPs) due to their unique physicochemical and biological properties. There is, however, a growing concern about their negative impact on male reproductive health. Therefore, in this work, a literature review was carried out to summarize current in vitro and in vivo studies that reported adverse effects of MONPs on the male reproductive system, to provide understanding of their toxicity through molecular, biochemical, and histopathological evidence. However, there are still limited data regarding the reversibility of this toxicity. To fully understand the impact of NPs on male reproductive health, it is crucial to determine if the induced damage is permanent. Therefore, the next step of this work was to assess the recovery ability of spermatogonia cells (GC-1 spg cell line) after 6 and 12 hours of exposure to a cytotoxic concentration of ZnO NPs. After a recovery period of 4 days where cells were left in NP-free conditions, cell viability results suggest that GC-1 cells were not able to fully recover from the induced damage. Thus, different concentrations (0-12.5 μM) of a synthetic chalcone (VS3) with antioxidant properties were used before and during GC-1 cells exposure to ZnO NPs in an attempt to mitigate the damage induced by NPs. The protective ability of this compound was evaluated through viability assays, intracellular detection of reactive oxygen species (ROS), DNA damage levels, and cytoskeleton protein levels (acetylated α-tubulin, β-tubulin, and β-actin). The results indicate that the tested concentrations of chalcone VS3 have the ability to attenuate the genotoxicity induced by ZnO NPs for shorter exposure periods (6 hours). VS3 supplementation also increased cell viability and stabilized microtubules. However, the antioxidant potential of this compound was inconclusive. In conclusion, this work addressed the main cytotoxic effects of MONPs on male reproductive cells and analyzed two different strategies to mitigate this damage, which represent a significant contribution in the field of male fertility. Future studies are planned with a view to a better understanding of the antioxidant potential of synthetic chalcone (VS3) in spermatogenesis.